Implementasi Waterfall dan Agile dalam Perancangan E-Commerce Alat Musik Berbasis Website - Putra, Wisnu Andika; Fitri, Iskandar; Hidayatullah, Deny (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The development of Information Technology (IT) is growing very rapidly. The rapid development of IT makes internet technology the main communication tool that is in great demand by the public. With the internet technology will facilitate and speed up the search for information, information is very important in supporting the course of a company to achieve the desired goals. Online transactions are a necessity that answers the problems that arise today. In online transactions, a person can freely make purchases, sales and find things he wants to do without having to meet with buyers or sellers through laptops, computer devices, or smartphones. For this reason, the authors design a web-based musical instrument sales system so that people can easily get information about selling musical instruments online quickly and precisely both regarding products, profiles, prices, and also how to shop at online stores and can directly make sales transactions. The author makes the design of this information system using UML (Unified Modeling Language), the Waterfall method, and Agile the author implements to create a website-based E-commerce application. As a result, users can shop and view information about musical instruments.